The inner journey: Views from the Hindu tradition - Case, Margaret H. (Sandpoint: Morning Light Press, 2007)
For over three decades, those for whom religion is a path of discovery and questioning have found insight in the pages of Parabola. This thoughtful anthology collects the magazine's best writings on Hinduism, featuring articles from Coomaraswamy, Easwaran, Aurobindo, Yogananda, and 20 other authors who vividly explore what it means to follow in this tradition. The collection combines poetry and folklore with incisive interviews and cogent essays on topics such as the search for self, attention and remembrance, transformational knowledge, and worldly and divine works. A lavish, full-color, 16-page set of plates brilliantly conveys the rich variety within the tradition